The timing of lawmaking - Fagan, Frank; Levmore, Saul, 1953-; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2017)
Legal reasoning, pronouncements of judgment, the design and implementation of statutes, and even constitution-making and discourse all depend on timing. This compelling study examines the diverse interactions between law and time, and provides important perspectives on how law's architecture can be understood through time. The book reconsiders older work on legal transitions and breaks new ground on timing rules, especially with respect to how judges, legislators and regulators use time as a tool when devising new rules. At its core, The Timing of Lawmaking goes directly to the heart of the most basic of legal debates: when should we respect the past, and when should we make a clean break for the future? This unique resource draws on examples from administrative law, banking law, budget law, constitutional law, criminal law, environmental law, inheritance law, national security law, tax law, and tort law, and will be of interest to academics studying law, political science and economics, as well as to policymakers, legislators, and judges.
Part I: Timing devices -- 1. Legal cycles and stabilization rules / Frank Fagan -- 2. Legislating crisis / David Kamin -- 3. The more it changes, the more it stays the same?: automatic indexing and current policy / Dan Shaviro -- 4. Racing the clock: deadlines, conflict, and negotiating in lawmaking / Daniel A. Farber -- 5. Playing for constitutional time: interim constitutions & transitional provisions / Tom Ginsburg and Eric Alston -- 6. Legislative sunrises: transitions, veiled commitments, and carbon taxes / Frank Fagan and Saul Levmore -- Part II: Law's architecture -- 7. The timing of consent / Jacob E. Gersen and Jeannie Suk -- 8. Interest groups and the durability of law / Saul Levmore -- 9. Self-executing statutes in the administrative state / Adam Samaha -- 10. Intellectual property and legislative innovation / Saul Levmore -- Part III: Time in judging -- 11. Janus-faced law: a philosophical debate / Martha C. Nussbaum -- 12. Renovating the efficiency of common law hypothesis / Frank Fagan -- 13. Delaying declarations of constitutional invalidity / Anthony Niblett -- 14. The sins of their fathers: illegitimacy in Japan and surrogate punishment across generations / J. Mark Ramseyer -- Index.
Contributors include: E. Alston, F. Fagan, D.A. Farber, J.E. Gersen, T. Ginsburg, D. Kamin, S. Levmore, A. Niblett, M.C. Nussbaum, E.A. Posner, J.M. Ramseyer, A.M. Samaha, D. Shaviro, J. Suk
Obsahuje bibliografie, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: zákonodárství; legislation; e-knihy online; e-books online